2020
DOI: 10.1039/d0ra02332a
|View full text |Cite
|
Sign up to set email alerts
|

Heat and pressure-resistant room temperature irreversible sealing of hybrid PDMS–thermoplastic microfluidic devices via carbon–nitrogen covalent bonding and its application in a continuous-flow polymerase chain reaction

Abstract: In this study, we have introduced a facile room-temperature strategy for irreversibly sealing polydimethylsiloxane to various thermoplastics using (3-aminopropyl)triethoxysilane (APTES) and [2-(3,4-epoxycyclohexyl)ethyl]trimethoxysilane (ECTMS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Borysiak et al reported maximum pressures of 4.1 bar without failure for bonding of SEBS to itself, PS, or glass surfaces applying 75 • C for 30 min [26]. When compared to PDMS bonded to itself [41], glass [42], or thermoplastics [43][44][45], similar or even higher values of bonding strength can be achieved using our presented TPE-based approach (Table 1), even after 7 days of exposure to buffer. Preventing the absorption of molecules from the solution into the bulk materials of the chips is of upmost importance due to the high surface-to-volume ratios seen in microfluidic systems, which can lead to the rapid drop of concentrations in the perfused solution [46].…”
Section: Device Bonding Strategiesmentioning
confidence: 54%
See 1 more Smart Citation
“…Borysiak et al reported maximum pressures of 4.1 bar without failure for bonding of SEBS to itself, PS, or glass surfaces applying 75 • C for 30 min [26]. When compared to PDMS bonded to itself [41], glass [42], or thermoplastics [43][44][45], similar or even higher values of bonding strength can be achieved using our presented TPE-based approach (Table 1), even after 7 days of exposure to buffer. Preventing the absorption of molecules from the solution into the bulk materials of the chips is of upmost importance due to the high surface-to-volume ratios seen in microfluidic systems, which can lead to the rapid drop of concentrations in the perfused solution [46].…”
Section: Device Bonding Strategiesmentioning
confidence: 54%
“…Borysiak et al reported maximum pressures of 4.1 bar without failure for bonding of SEBS to itself, PS, or glass surfaces applying 75 °C for 30 min [ 26 ]. When compared to PDMS bonded to itself [ 41 ], glass [ 42 ], or thermoplastics [ 43 , 44 , 45 ], similar or even higher values of bonding strength can be achieved using our presented TPE-based approach ( Table 1 ), even after 7 days of exposure to buffer.…”
Section: Resultsmentioning
confidence: 91%
“…Since there is an additional chemical reagent or layer applied in the bonding interface to increase the surface energy or enhance bonding strength of the microfluidic device, this method is defined as indirect bonding method. For chemical surface modification, chemical reagents such as APTES [ 147 , 148 ], [2-(3,4-epoxycyclohexyl)ethyl]trimethoxysilane (ECTMS) [ 147 ], (3-triethoxysilyl)propylsuccinic anhydride (TESPSA) [ 148 ] and 3-(trimethoxysilyl)propyl methacrylate (TMSPMA) [ 149 ] are used. These chemicals increase surface energy of the substrates and bind them through the formation of strong covalent bond between reagents and substrates.…”
Section: Indirect Bondingmentioning
confidence: 99%
“…These chemicals increase surface energy of the substrates and bind them through the formation of strong covalent bond between reagents and substrates. The schematic process for bonding PDMS modified using ECTMS with thermoplastics treated with APTES and ECTMS is shown in Figure 7 [ 147 ]. The high quality bond between PDMS and thermoplastics is obtained by the strong covalent carbon–nitrogen bonding using silane reagents.…”
Section: Indirect Bondingmentioning
confidence: 99%
“…Lab on PCB (LOP) is the future of microfluidics; its globally available equipment and techniques enable the production of inexpensive disposable devices. Among the recent works on PDMS-PCB bonding are; half-cured PDMS technique on rigid PCB for construction of continuous-flow PCR [13], polyimide to PDMS bonding with thin-film SiO2 [14], and surface functionalized PDMS bonding to several plastic substrates [15,16]. The former device, the continuous-flow PCR [13], used PDMS as a planarization layer to encase the electronics components on the printed circuit board, whereas the latter three are the other indirect bonding methods for flexible plastic PCB-PDMS pair substrates.…”
Section: Introductionmentioning
confidence: 99%